Interleukin-10 and interferon-γ modulate surface expression of fractalkine-receptor (CX3CR1) via PI3K in monocytes - Ramos, Maria Victoria (2010)
The membrane-anchored form of the chemokine fractalkine (CX3CL1) has been identified as a novel adhesion molecule that interacts with its specific receptor (CX3CR1) expressed in monocytes, T cells and natural killer cells to induce adhesion. In addition, CX3CL1 can be cleaved from the cell membrane to induce chemotaxis of CX3CR1- expressing leucocytes. Recently, marked variations in CX3CR1 monocyte expression have been observed during several pathological conditions. Regulation of CX3CR1 in monocytes during basal or inflammatory/anti-inflammatory conditions is poorly understood. The aim of this study was therefore to examine CX3CR1 expression during monocyte maturation and the effect of soluble mediators on this process. We found that basal expression of CX3CR1 in fresh monocytes was reduced during culture, and that lipopolysacchairde accelerated this effect. In contrast, interleukin-10 and interferon-γ treatment abrogated CX3CR1 down-modulation, through a phosphatidylinositol 3 kinase-dependent pathway. Most importantly, CX3CR1 membrane expression correlated with monocyte CX3CL1-dependent function. Taken together, our data demonstrate that CX3CR1 expression in monocytes can be modulated, and suggest that alterations in their environment are able to influence CX3CL1- dependent functions, such as chemotaxis and adhesion, leading to changes in the kinetics, composition and/or functional status of the leucocyte infiltrate. © 2010 The Authors.